Impact of Cultivation Practices and Varieties on Productivity, Profitability, and Nutrient Uptake of Rice (Oryza sativa L.) and Wheat (Triticum aestivum L.) Cropping System in India - Saini, Ankit; Manuja, Sandeep; Kumar, Suresh; Hafeez, Aqsa; Ali, Baber; Poczai, Peter (Agriculture (Basel), 2022)
Interest in conservation measures, including reduced tillage, zero tillage, and crop residue retention, is growing in major rice growing areas of the world; particularly in the Indo-Gangetic plains. Of late, research interest is increasing in India for a specialised method of cultivation known as natural farming, which aims at maintain the functional biodiversity of the farm with little or no use of external inputs. With the increasing water crisis at a global level, it became imperative to develop technologies that can reduce the water use, particularly in water-guzzling low land paddy, by developing alternate cultivation methods; direct seeded rice is one such technology. A two-year field experiment was carried out at two locations during 2019–2020 and 2020–2021 to find out the impact of different cultivation and varieties on the productivity and profitability of the rice–wheat cropping system. The experiments were conducted in split plot design, replicated thrice, with cultivation practices in the main plot and varieties of both wheat and rice in the sub plot. The results so obtained reveal that conventional tillage significantly out yielded other methods of cultivation in both the crops at both the locations, while significantly lower grain yield in both crops was observed from natural farming. Adoption of reduced tillage, zero tillage and natural farming reduced the grain yield of wheat by 4.6%, 10.9%, and 59.4% over conventional tillage, while the corresponding decline in grain yield of rice was 10.8%, 16.1%, and 34.0% with reduced tillage, zero tillage, and natural farming, respectively. Among the varieties tested, HPW 368 and Him Palam Lal Dhan 1 (HPR 2795) produced significantly higher grain yield of wheat and rice, respectively, at both the locations during both years. Conventional tillage among cultivation practices and HPW 368 and Him Palam Lal Dhan 1 (HPR 2795) among wheat and rice varieties also proved to be better in terms of various economic indicators, including gross return, net return, and ratio benefit cost ratio (B:C ratio).